Comparison between conservative and surgical management of ingrown toenail in Bangladeshi patients - Khan, M. Rashiduzzaman; Siddique, Mohammad R. U. (International Journal of Research in Dermatology, 2025)
Background: Ingrown toenail (onychocryptosis) is a common and painful condition that affects daily activities and quality of life. Treatment options include conservative and surgical interventions, with varying efficacy and patient outcomes. This study aimed to compare the effectiveness of conservative versus surgical management of ingrown toenails in Bangladeshi patients. Methods: This prospective observational study was conducted at the Nail Unit, Aurora Skin and Aesthetic Center, Dhaka, over six months (10 January to 09 July 2024). A total of 100 patients with clinically diagnosed ingrown toenail were enrolled and equally divided into two groups: 50 patients received conservative treatment (topical antibiotics, proper nail trimming, and footwear advice) and 50 underwent surgical intervention (partial nail avulsion with/without matrixectomy). Outcomes measured included healing rate, healing time, pain reduction (VAS), recurrence, infection, patient satisfaction, and work/school absenteeism. Data were analyzed using statistical package for the social sciences (SPSS) version 25. Results: The groups were comparable in terms of age, sex, affected toe, and disease severity. Surgical treatment showed significantly better outcomes: complete healing in 94% versus 78% (p=0.02), shorter mean healing time (10.1±2.7 versus 13.5±3.2 days; p<0.001), greater pain reduction (VAS: 5.1 versus 4.2; p=0.001), and lower recurrence (4% versus 18%; p=0.03). Patient satisfaction was higher in the surgical group (92% versus 68%; p=0.003), with fewer missed workdays and repeat visits. Conclusion: Surgical management of ingrown toenails provides superior outcomes in terms of healing, pain relief, and recurrence compared to conservative treatment, and should be considered for definitive management.